RANCANG BANGUN ALAT PENDETEKSI GAS BERBAHAYA (GAS CO_2, NOx, DAN HC) BERBASIS IOT - Surojo, Surojo; Randa, Apri; Arwin, Rifan Muazin; Br Sebayang, Monischa (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The increase in industrial activities and motor vehicle usage has led to high emissions of hazardous gases which can negatively impact human health and the environment. Therefore, an effective and real-time gas monitoring system is needed. This study aims to design and develop a hazardous gas detection device based on the Internet of Things (IoT) capable of continuously monitoring CO₂, NOx, and HC concentrations. The system uses MQ-series gas sensors integrated with an ESP32 microcontroller as the main data processor, along with an IoT platform to display measurement results online through a dashboard. The collected data can be accessed in real time via the internet, allowing users to monitor remotely. Testing results show that the device can detect gas concentration changes with good accuracy and fast response time. This tool is expected to assist in early detection of air pollution and raise awareness of the importance of healthy air quality.